(Re)constructing Leadership: Complexity and Flexibility - Toh, Seong-Yuen * (IGI Global, 2022)
This chapter elucidates Keith Grint's model of leadership as a viable dynamic option in our complex world. By locating the model within a social constructionist frame, this chapter demonstrates how far we have come in the evolving stream of leadership research. Seven main characteristics of the Grint's model of leadership are discussed to demonstrate how the model can help us to understand wicked problems, such as the COVID-19 pandemic in Malaysia. The author also identifies two weaknesses of Grint's model: (1) organisational culture and (2) followership. Lastly, to address the two weaknesses, the author proposes an integrated model of leadership that combines the understanding of an adhocracy culture based on the competing value framework and Kelly's effective followership model. In conclusion, the integrative framework of leadership offers leadership researchers a model with more explanatory power in understanding the leadership phenomenon within the social constructionist supposition.